Dissolved Gas Analysis (DGA) Testing Analysis on 150kv Power Transformers - Muhammad Rivai; Muhammad Erpandi Dalimunthe; Dino Erivianto (Sean Institute, 2025)
This research used a laboratory experimental method with a quantitative approach. The aim was to measure and analyze the dissolved gas content in power transformer oil and to explain the measurement results based on the IEEE C57.104-2008 standard and PT PLN's Decree No. 0520 K/DIR/2014. The research objects were Power Transformers 1 and 2 of the 150 kV Titi Kuning Substation on Jalan Suka Tirta No. 54b, Medan, North Sumatra. The analysis used two methods to determine the condition of this transformer: TDCG and Key Gases. The first method is to measure the contents of Hydrogen (H2), Acetylene (CH2), Ethylene(CH4), Ethane (CH6), Methane, Carbon monoxide (CO), and Carbon dioxide (CO2). The second method involves summing the values of Gas Chromatography Method (TDCG) for Dissolved Gas Analysis (DGA) analysis, and the third method is a key gas method for determining the type of damage or abnormalities in a transformer.